Preliminary Study on the Potential of Harvesting Energy from Malaysian Road Pavement - Wan Abdullah Sani, Wan Muhammad Aiman (Universiti Teknologi PETRONAS, 2017)
Unused energy occurred at the pavement in the form of solar radiation, vibration and stress have the potential to be converted into more useful energy mainly into electrical energy. It is an alternative way to produce renewable energy source for electricity generation in order to replace the depleting non-renewable energy resources. This paper is to review and evaluate different methods of harvesting energy from road pavement as well as to identify the most promising method to be used for Malaysia road. Evaluation on the efficiency and cost-analysis are done based on the information of current harvesting energy technologies which are piezoelectric and photovoltaic energy harvesters. Secondary data such as average daily traffic (ADT) in Malaysia expressways and average annual solar radiation in Malaysia are collected in order to identify the real potential of harvesting energy from Malaysia pavement.